Cost Effective Rotary to Linear Motion Conversion for a Near Omni-Directional Robotic Vehicle - Masum, H (International Journal of Computer Sciences and Engineering, 2025)
The near omni-directional hexapod vehicle is an autonomous robotic kit which can move in three-dimensional space. It is able to rotate any angle at its any state of movement without compromising its speed. Rotary-to-linear motion conversion is concerned with taking the rotational motion and torque from an actuator and producing a linear motion and force on the output. In this paper, an effort has been made to design the mechanical system of a robotic vehicle having six legs which can serve as a compliant mobile platform. The design has been validated through simulation. It has a limited number of degreeof-freedom to minimize the mechanical motion constraints as well as lower power consumption. The hexapod design of the vehicle offers great static stability during walking.